Implementation Of Sharia Economic Principles Towards Economic Growth - Melki Gustinor; La Ode Muhamad Safar (Global Scientific Publishing, 2023)
Sharia Economics is continuous knowledge develop follow development system economy and development modern technology today This . This article try deepen and understand How development Islamic economics in the world and how implementation Islamic economics in industry world finance . This article use method study literature For dig various study previous studies and literature relevant . In terms of this , article This discuss draft base Islamic economics , principles and instruments Islamic finance , as well How principles This implemented and put into practice in industry global finance . Development economy No regardless from obstacles faced in its application in the field . Findings from study This show that application principle sharia economics can help realize system more finances stable , fair and sustainable . Additionally , the article this also identifies a number of challenges and obstacles in application principles this and offer a number of conclusion For study more carry on in field This . In order to finish existing obstacles so required various device rules and regulations . Development and release regulations can also be done influenced by the prevailing political system
Keywords: Implementation Principles of Sharia Economics; Development of Shari; Sharia Economics in Indonesia